Robert H. Bork papers - Bork, Robert H.
Personal and official correspondence, lectures, legal briefs and opinions, legal case files, memoranda, speeches, writings, research notes, and other papers documenting Bork's career as a lawyer, legal scholar, professor of law, and federal appellate court judge. Includes material on antitrust law, legislative encroachments, the role of the Supreme Court in capitalist society, and the Watergate Affair, particularly Bork's firing of special prosecutor Archibald Cox; Bork's affiliation with Yale Law School, the U.S. Dept. of Justice, and the American Enterprise Institute for Public Policy Research; his association with Alexander M. Bickel and the Freedom of Information Act; and the failure of Bork's nomination to the Supreme Court in 1987. Correspondents include William J. Baroody, Alexander M. Bickel, James H. Billington, Hammond E. Chaffetz, Charles W. Colson, Edward De Grazia, Milton Friedman, Barry Goldwater, Alexander Meigs Haig, H.R. Haldeman, Howard G. Krane, Irving Kristol, Thomas B. Leary, Edward H. Levi, Thurgood Marshall, Abner J. Mikva, Richard M. Nixon, Bernard J. Nussbaum, Benjamin H. Read, Donald H. Rivkin, Frederick M. Rowe, and Lawrence E. Walsh.
Lawyer, educator, and judge. Full name: Robert Heron Bork. Born 1927; died 2012.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baroody, William J., -- 1916-1980 -- Correspondence; Bickel, Alexander M; Bickel, Alexander M. -- Correspondence; Billington, James H. -- Correspondence; Chaffetz, Hammond E. -- Correspondence; Colson, Charles W. -- Correspondence; Cox, Archibald, -- 1912-2004.; De Grazia, Edward, -- 1927-2013 -- Correspondence; Friedman, Milton, -- 1912-2006 -- Correspondence; Goldwater, Barry M. -- 1909-1998 -- Correspondence; Haig, Alexander Meigs, -- 1924-2010 -- Correspondence; Haldeman, H. R. -- 1926-1993 -- Correspondence; Krane, Howard G. -- Correspondence; Kristol, Irving -- Correspondence; Leary. Thomas B. -- 1931- -- Correspondence; Levi, Edward H. -- 1911-2000 -- Correspondence; Marshall, Thurgood, -- 1908-1993 -- Correspondence; Mikva, Abner J. -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Nussbaum, Bernard J., -- 1931- -- Correspondence; Read, Benjamin H. -- 1925- -- Correspondence; Rivkin, Donald H. -- 1924- -- Correspondence; Rowe, Frederick M. -- Correspondence; Walsh, Lawrence E. -- Correspondence; American Enterprise Institute for Public Policy Research; United States. -- Department of Justice; United States; United States. -- Supreme Court; Yale Law School; Antitrust law -- United States; Appellate courts -- United States; Capitalism -- United States; Law -- Study and teaching; Legislative power -- United States; Watergate Affair, 1972-1974.; Educators; Jurists; Lawyers